The Marine Endophytic Polyamine-Producing Streptomyces mutabilis UAE1 Isolated From Extreme Niches in the Arabian Gulf Promotes the Performance of Mangrove (Avicennia marina) Seedlings Under Greenhouse Conditions - El-Tarabily, Khaled A.; Ramadan, Gaber A.; Elbadawi, Alaa A.; Hassan, Amira H.; Tariq, Saeed; Ghazal, Eman W.; Abo Gamar, Mohammad I.; AbuQamar, Synan F. (Frontiers in Marine Science, 2021)
Mangrove forests in the Arabian Gulf are under continuous threat. To increase plantations of gray mangrove (Avicennia marina) in the United Arab Emirates (UAE), 27 endophytic actinobacterial isolates obtained from mangrove roots were in vitro pre-screened to detect the polyamines (PAs) [putrescine (Put), spermidine (Spd), and spermine (Spm)]. We also determined the abilities of the endophytic PA-producing actinobacterial isolates in enhancing the growth of A. marina under greenhouse conditions. Although three highly PA-producing isolates were recovered from inside mangrove root tissues, Streptomyces mutabilis UAE1 constantly colonized root and stem inner tissues for 12 weeks, suggesting an endophytic association between this actinobacterial isolate and mangrove seedlings. When roots were inoculated with S. mutabilis, mangrove growth was remarkably enhanced under gnotobiotic and greenhouse conditions. This was evident from the significant (P < 0.05) increases in dry weight and length of root (66.7 and 65.5%, respectively) and shoot (64.8 and 58.0%, respectively), number of branches (64.3%), total leaf area (40.2%), and photosynthetic pigments (54.5% chlorophyll a; 40.0% chlorophyll b; and 53.1% carotenoids) of mangrove compared to the PA-non-producing Streptomyces sp. or control treatment. Growth promotion in plants treated with S. mutabilis was also supported by significant (P < 0.05) elevations in the contents of mangrove in planta PAs, auxins, and cytokinins, accompanied by a decrease in abscisic acid levels. No difference was, however, detected in growth and amounts of PAs or any plant growth regulators (PGRs) in plants treated with or without the PA-non-producing isolate. Our findings indicate that plant growth parameters can be enhanced as a consequence of secretion of Put, Spd, and Spm by S. mutabilis resulting in regulation of endogenous PAs and other PGRs in mangrove tissues. This study is the first record that aims to improve sustainable agricultural management practices using plant growth promoting (PGP) actinobacteria, endophytic in mangrove tissues to promote mangrove growth under greenhouse conditions. Such research may allow this region to be a model to study the synergistic S. mutabilis–mangrove interactions and the future impacts on mangrove reforestation in the Arabian Gulf and elsewhere where mangrove forests are in threat.